SDF-1 and NOTCH signaling in myogenic cell differentiation: the role of miRNA10a, 425, and 5100 - Bartosz Mierzejewski; Iwona Grabowska; Zuzanna Michalska; Kamila Zdunczyk; Franciszek Zareba; Aliksandra Irhashava; Marta Chrzaszcz; Magdalena Patrycy; Wladyslawa Streminska; Katarzyna Janczyk-Ilach; Marta Koblowska; Roksana Iwanicka-Nowicka; et al. (Stem Cell Research & Therapy, 2023)
Abstract Background Skeletal muscle regeneration is a complex process regulated by many cytokines and growth factors. Among the important signaling pathways regulating the myogenic cell identity are these involving SDF-1 and NOTCH. SDF-1 participates in cell mobilization and acts as an important chemoattractant. NOTCH, on the other hand, controls cell activation and myogenic determination of satellite cells. Knowledge about the interaction between SDF-1 and NOTCH signaling is limited. Methods We analyzed two populations of myogenic cells isolated from mouse skeletal muscle, that is, myoblasts derived from satellite cells (SCs) and muscle interstitial progenitor cells (MIPCs). First, microRNA level changes in response to SDF-1 treatment were analyzed with next-generation sequencing (NGS). Second, myogenic cells, i.e., SC-derived myoblasts and MIPCs were transfected with miRNA mimics, selected on the basis of NGS results, or their inhibitors. Transcriptional changes, as well as proliferation, migration, and differentiation abilities of SC-derived myoblasts and MIPCs, were analyzed in vitro. Naive myogenic potential was assessed in vivo, using subcutaneous engrafts and analysis of cell contribution to regeneration of the skeletal muscles. Results SDF-1 treatment led to down-regulation of miR10a, miR151, miR425, and miR5100 in myoblasts. Interestingly, miR10a, miR425, and miR5100 regulated the expression of factors involved in the NOTCH signaling pathway, including Dll1, Jag2, and NICD. Furthermore, miR10a, miR425, and miR5100 down-regulated the expression of factors involved in cell migration: Acta1, MMP12, and FAK, myogenic differentiation: Pax7, Myf5, Myod, Mef2c, Myog, Musk, and Myh3. However, these changes did not significantly affect myogenic cell migration or fusion either in vitro or in vivo, except when miR425 was overexpressed, or miR5100 inhibitor was used. These two molecules increased the fusion of MIPCs and myoblasts, respectively. Furthermore, miR425-transfected MIPC transplantation into injured skeletal muscle resulted in more efficient regeneration, compared to control cell transplantation. However, skeletal muscles that were injected with miR10a transfected myoblasts regenerated less efficiently. Conclusions SDF-1 down-regulates miR10a, miR425, and miR5100, what could affect NOTCH signaling, differentiation of myogenic cells, and their participation in skeletal muscle regeneration.